"Music Theatre Now – Global Tendencies and Perspectives", in Music Theatre Now – Programme of the 2016 Meeting at the Operadagen Rotterdam, 2016, pp. 10-19. - Roesner, David (Zenodo, 2016)
Music Theatre Now is acompetition and subsequentfestival organised by the International Theatre Institiute, whichcelebrates new music theatre from around the Globe. Every three years, practitioners are invited to submitted video documentations, scores and libretti of new worksthat have been performed at least once. In 2015 an internationaljury picked 14 from more than 450 submission which they foundparticularly original, innovative and of high quality. The production came from China, Italy, Russia, Germany, Belgium, Iceland, USA, Mexico, Argentina and Australia. This selection provides, despite all its diversity, afascinating prism through which to trace somecontemporary developments and aesthetic departures, which –particularlywhen read against theEuropean canon of the operatic tradition – are interesting to look at in more detail. In this festival programme contribution, David Roesner will examine examples of theseproduction and try to teaseout some of the share characteristics of what is new and noteworthy about thisselection.